PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP MINAT PEMBELIAN KRIPIK TEMPE SAWANGAN NO 1 DI PURWOKERTO - Nugroho, Widi Ardhiyan; Hidayah, Arini (Media Ekonomi, 2015)
This research was entitled “the effects of Product Quality, Price, and Promotion toward the purchasing interest of Kripik Tempe Sawangan No 1 in Purwokerto”. This research aimed to analyze the effects of product quality, price, and promotion toward the purchasing interest of Kripik Tempe. In this research, the data collection was done by questionnaires given to 100 respondents of Kripik Sawangan No 1 in Purwokerto through accidental sampling method to know the respondens response towards each variable. The technique of data analysis used double linear regression analysis that was used to prove the research hypothesis. The data that fulfilled the validity, reliability, classical assumption tests was analyzed to produce the equation of double linear regression. This research results could be concluded that product quality, price, and promotion gave positive effects towards purchasing interest of Kripik Tempe. The test of hypothesis used t-test and showed that product quality, price, and promotion as analyzed variables were significantly proven affected the variable of purchasing interest. Key words: product quality, price, promotion, and purchasing interest.